PELATIHAN PEMBUATAN PAKAN ALTERNATIF BERBAHAN SAYURAN TERFERMENTASI UNTUK MENINGKATKAN KESEHATAN TERNAK - Azhari, Azhari; Muslinawati, Retno; Muda Agam Sakti, Tengku; Alfiyana, Siti (Jurnal Abdi Masyarakat, 2024)
Utilizing vegetables as animal feed obtained from the yard is a practical and economical solution to meet the nutritional needs of livestock. Planting various types of vegetables such as kale, spinach, and cassava in the yard not only provides a source of fresh food for the family, but can also be processed into quality animal feed. The process of processing vegetables is done by blending until smooth and mixing with a little water. To increase the nutritional content, this mixture can be added with fine bran or flour, then stirred until evenly distributed. This processed feed is easily digested by livestock, thus helping to optimize nutrient absorption. Utilizing the yard to grow animal feed vegetables also supports sustainable agricultural practices and reduces dependence on commercial feed that may contain chemicals.